Personal Data Protection in Political Party Information Systems in the Organization of General Elections: Concept and Law Reform Recommendations - Erman I. Rahim; Mohamad Afriyansyah Dukalang; Abdul Hamid Tome; Nuvazria Achir; Souad Ezzerouali (Journal of Law and Legal Reform, 2025)
Exploiting citizens’ personal data by political parties within the Political Party Information System (SIPOL) database during the 2024 General Election has adversely affected the public. This paper examines the exploitation of citizens’ personal data by political parties via identity fraud from a legal standpoint, while also suggesting a framework for personal data protection and legal change. The primary aim is to offer conceptual proposals for safeguarding people’s personal data inside SIPOL and to suggest legal revisions to the Election Law and Political Party Law, therefore integrating requirements for personal data protection into the Personal Data Protection Law. This study utilized normative legal research methodologies, including a statute, case, and conceptual approach, to address the legal issues under examination. The research findings indicated that the illicit utilization of citizens’ personal data for political party membership adversely affects the individuals involved and constitutes a legal infraction. This article provides a framework for safeguarding people’s personal data within the SIPOL, alongside legal revisions to the Election Law and Political Party Law, which policymakers can address.